1988
DOI: 10.1007/bf02142570
|View full text |Cite
|
Sign up to set email alerts
|

The effect of compound 48/80 and of electrical field stimulation on mast cells in the isolated mouse stomach

Abstract: It has been shown that compound 48/80 evokes acid secretion in the isolated mouse stomach by releasing histamine from mast cells. The aim of the present work was to study the distribution and type of mast cells in the isolated mouse stomach and to examine the effect of compound 48/80 and of electrical field stimulation (EFS) on these cells. Histological examination of the stomachs showed only the presence of connective tissue mast cells (CTMC) in all parts of the stomach except in the glandular mucosa where mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Iurina et al (79) suggested that the high magnetic sensitivity of MCs revealed in their study could be used as a test of body reactivity and adaptation to this physical agent! Finally, there are also reports indicating tissue-specific effects (80) as well as the appearance of EMF-modulating effects on the number of mast cells in healing skin (81). However, also single studies finding a lack of such biophysical correlations are found in the literature (see e.g.…”
Section: Direct Effects Of Emfs On Mast Cellsmentioning
confidence: 97%
“…Iurina et al (79) suggested that the high magnetic sensitivity of MCs revealed in their study could be used as a test of body reactivity and adaptation to this physical agent! Finally, there are also reports indicating tissue-specific effects (80) as well as the appearance of EMF-modulating effects on the number of mast cells in healing skin (81). However, also single studies finding a lack of such biophysical correlations are found in the literature (see e.g.…”
Section: Direct Effects Of Emfs On Mast Cellsmentioning
confidence: 97%
“…Similarly, CTMCs were also identified in the mouse gastric submucosa. 31 Of note, C48/80, which is shown as an effective adjuvant following IN immunizations, 8,10 selectively activates CTMCs but not MMCs 26,45,46 and, hence, it has to penetrate ''deep'' into the submucosa to reach the CTMCs. Furthermore, differential responsiveness of CTMCs and MMCs to other stimuli has also been described.…”
Section: Toluidine Bluementioning
confidence: 99%
“…MC were counted and the percentage of degranulated MC was determined in 200 cells for each preparation. MC were identified and their degranulation assessed by morphological criteria [7].…”
Section: Methodsmentioning
confidence: 99%